Evaluation of Genetic Diversity of Wild Raspberry Genotypes in the Western Caspian Sea Regions by ISSR Molecular Markers - Mohammad Fatemi; Asghar Estaji; Alireza Ghanbari; Mousa Torabi Giglou; Maryam Jamali (Journal of Genetic Resources, 2025)
The raspberry is an edible fruit belonging to the Rubus genus within the Rosaceae family. The species is known for its high global genetic diversity. Raspberries are highly regarded for their nutritional benefits, particularly their contributions to dietary fiber and vitamins. This species contains numerous wild genotypes, and it is essential to discover and investigate them in this experiment. Managing natural diversity in domestic cultivars and wild relatives plays a crucial role in creating targeted programs to improve plant products. The study aims to identify and examine various wild genotypes within this species. For this, 48 wild raspberry genotypes were gathered from multiple locations along the western borders of the Caspian Sea forests, specifically from Fandoghlo, Astara, Germi, and Bilesavar in Iran. The genetic diversity of these genotypes was assessed using 12 ISSR primers. The analysis of the observed bands revealed a significant range of polymorphism, varying from 33% to 100%, with an average polymorphism rate of 77%. Based on cluster analysis results, the genotypes were classified into three main clusters. The first and second cluster analysis groups were located in the west and southwest of the Caspian Sea. The findings of this research indicated that there is sufficient genetic diversity between raspberry wild genotypes, which is largely affected by the geographical regions of the genotypes. Certainly, regions that were more distantly located exhibited a higher genetic diversity between their genotypes. This phenomenon can be attributed to the role of cross-pollination facilitated by insects, as well as the influence of natural barriers.